Trends in rates and causes of hospitalization among people living with HIV in the antiretroviral therapy era: A retrospective cohort study in China, 2008–2020 - Liu, Ying; Hao, Yiwei; Xiao, Jiang; Wu, Liang; Liang, Hongyuan; Han, Junyan; Zhao, Hongxin (Frontiers in Public Health, 2022)
Background: The introduction of antiretroviral therapy (ART) has resulted in marked reductions in morbidity among people living with HIV (PLWH). Monitoring the hospitalizations of PLWH is important in evaluating the quality of healthcare and forecasting the co-morbidity pattern. We aimed to describe the trends in the rates and causes of hospitalization among PLWH who initiated ART in a HIV designated hospital in China. Methods: PLWH, who initiated ART and were hospitalized in Beijing Ditan Hospital from 2008 to 2020, were selected. Hospitalizations were classified based on AIDS-defining events (ADEs), non-AIDS-defining events (nADEs), and other causes. Hospitalization rates were calculated in terms of person-years, with risk factors determined by Poisson regression. Proportion of hospitalization causes at different ART treatment statuses was also evaluated. Results: A total of 9 404 included patients (94.7% were males) contributed 49 419 person-years. Overall, 1 551 PLWH were hospitalized for 2 667 hospitalization events. 60.4% of hospitalizations were due to ADEs, 11.4% were due to nADEs, and 28.2% were due to other causes. Unadjusted hospitalization rates decreased for all causes and all three diagnostic categories by year. After adjusting for the variables that changed substantially over time, ADE-related [IRR, 1.01 (0.96-1.05)] and nADE-related hospitalization rates [IRR, 0.92 (0.84-1.01)] appeared stable. Hospitalization for ADEs constituted an increasing proportion over time (36.3% in 2008 to 57.4% in 2020), especially in ART-naive inpatients (43.8% in 2008 to 83.3% in 2020). The proportion of nADE-related hospitalizations remained low (9.0% in 2008 to 15.4% in 2020). Hospitalization was highest for patients treated with ART during the first 6 months after ART initiation (46.2%) when ADEs were still the leading cause of hospitalizations (30.6%). Older age, non-man who have sex with man transmission, late presenters, VL > 50 copies/mL, and CD4 ≤ 200 cells/µL were associated with a higher hospitalization risk (all P value < 0.05). Conclusion: Despite some progress, ADEs remain the most common and serious problem among PLWH in China. In order to avoid deteriorating to the stage of needing hospitalization, more work is needed to diagnose and treat HIV infection earlier.